Strengthening the development of Qur’anic schools and student profiles about Pancasila during the pandemic - Hidayah, Yayuk (Journal of Community Service and Empowerment, 2021)
Learning in the mass of the Covid-19 pandemic requires various innovations and management to stay in line with the direction and goals in education. The purpose of this service is to increase the understanding of TPA teachers (ustadz / ustadzah) to develop Taman Pendidikan Al-Qur’an/TPA (Qur’anic school) and learning during the pandemic as well as to strengthen the profile of Pancasila Students. The service was carried out by a team from the Department of Primary School Teacher Education, Universitas Ahmad Dahlan during a month. Based on the dedication carried out, it is known that there has been an increase in understanding of TPA development and learning during the pandemic. This event also produces TPA management documents. Based on this dedication, it can be concluded that the understanding of TPA teachers to develop TPA and learning during the pandemic has increased. It is hoped that the continuity of this service activity is that there is a continuation of cooperation to increase the understanding of TPA teachers to develop TPA and learning during the pandemic as well as to strengthen the profile of Pancasila Students.